Influence of different additives on the creep property of oil well cement - Song, Meimei; Gao, Yang; Zhang, Yafei (Frontiers in Built Environment, 2022)
As the exploitation of oil and gas field becomes more difficulty nowadays, severe casing deformation may occur if anti-extrusion strength of casing decreases to a certain degree and this brings large economic loss and severe safety problems. As an annular sheath between casing and formation, creep of oil well cement paste is one of the most important factors in deciding abnormal casing deformation and wellbore integrity. To figure out the mechanism on how to reduce the creep value of oil well cement paste, effect of different additives e.g. retarder, glass fibre reinforcement and CSA expansive agent on the creep value of oil well cement are investigated in this study. It can be found out that retarder plays a negative role in reducing the creep deformation and creep value of cement with 1, 2, 3% retarder is 2.39%, 7.85% and 15.02% higher than that without retarder at 12h. Results from heat flow indicates that retarder may play an important role in prolonging the early induction period of hydration and reducing the hydration rate in the middle and later stages. On the contrary, Glass fibre shows a positive effect in reducing the creep value of oil well cement paste and creep value reaches with 0.2%, 0.4%, 0.6% and 0.8% is 1.27%, 6.61%, 9.82% and 12.60% lower than that without fibre addition at 72h. This is because high porosity between and around fibers based on a microstructure observation may lead to a more continuous and uniform stress field between cement paste, and consequently reduce the creep value of cement paste. It can also be found out that CSA cement is considerably effective in limiting creep deformation of oil well cement paste at early ages. There is also an acceleration effect on the heat flow of oil well cement in both induction and acceleration periods and the corresponding maximum heat flow is 7.3%, 9.0% and 11.2% higher than the reference cement with no CSA addition. The results obtained in this study are aimed to provide theoretical basis for the wellbore integrity and improvement of oil and gas recovery.